Sensitivity of Some Apple Varieties Grown in Regions of Al-Jabal Al-Akhdar to Apple Scab Disease - Albarani, Majuldeen F.; Mohamed, Nwara A.; Saeed, Mohammed A. (Al-Mukhtar Journal of Sciences, 2022)
The study aimed to know the extent of infection of apple varieties grown in Al-Jabal Al-Akhdar regions with apple scab disease during the seasons 2018-2019. The results showed the incidence of the disease was higher in August in Al-Bayda, Shahat, and Al-Marj, at a rate of 73, 72, and 61.7%, respectively, while it was higher in September in the regions of Al-Kuf and Qandula, at a rate of 79.6, and 73.2%, respectively. The study showed the highest infection rate was among the local variety, with a rate of 86% and a severity of 41%, followed by Starking variety, with 77% in 2018 season. As for 2019 season, the Local variety was the most infected, with a rate of 80% and a severity at 43%. The study showed the relationship between the percentage of the disease and its severity with the environmental conditions, results showed that the relationship between the incidence of disease and temperature in Al-Bayda was weak (r = 0.15), as well as between the severity of the disease and relative humidity (r = 0.081). We conclude that the cultivars in the study area are sensitive to the disease, and Golden Delicious cultivar is more susceptible to infection.